The 1956 Hungarian revolution and its aftermath from the point of view of the Transcarpathian archival documents - Natalia Varadi; Вароді Наталія; Váradi Natália (ORT Publishing, 2019)
Abstract. The Hungarian revolution of 1956 is the event of Hungarian history that gave Hungary the biggest role in world politics in the last century. Many works were born based on its story, both in Hungary and abroad. The materials from the archives of the late Soviet Union, including Ukraine, and Transcarpathia, are mostly undiscovered, a significant amount is still classified. Two archives refer to the Transcarpathian relations of the revolution of 1956, the State Archives of the Transcarpathian Region and in the Uzhgorod‘s archive of the Ukrainian Committee for State Security. The records in both archives are mostly about the retaliation after the revolution.
Keywords: Soviet Union; Transcarpathia; deportations; Hungarian revolution of 1956